1997
DOI: 10.1111/j.1095-8312.1997.tb01782.x
|View full text |Cite
|
Sign up to set email alerts
|

Shell variation in sympatric freshwater Lymnaea peregra and L. ovata (Gastropoda: Lymnaeidae)

Abstract: Snails of the genus Lymnaea are morphologically variable and their taxonomy is unclear. In particular, the forms peregra and ovata, distinguished by shell shape, are often considered variants of the same species, L. peregra. We studied a rare situation in a Swiss mountain lake where both forms are sympatric. First, we found that the forms shows complete separation for a number of allozymes. Second, we examined the response of the two snail forms to infection by the trematode Diplostomum phoxini. For the ovata … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 21 publications
1
18
1
Order By: Relevance
“…Hubendick (1951) considered the latter as a synonym of R. peregra, a view that also appears to have been adopted by Jackiewicz (1993) in her morphologicalsystematic study of European lymnaeids. In contrast, shell morphology and allozyme data indicated that R. peregra and R. ovata are distinct (Glo¨er et al 1987;Ward et al 1997), which is concordant with the 16S data since sequence divergence between these two species is relatively large (8.9%). The tree topologies further show that R. ovata is more closely allied to R. auricularia (bs=76-98%; di=2) than it is to R. peregra.…”
Section: Resultssupporting
confidence: 58%
“…Hubendick (1951) considered the latter as a synonym of R. peregra, a view that also appears to have been adopted by Jackiewicz (1993) in her morphologicalsystematic study of European lymnaeids. In contrast, shell morphology and allozyme data indicated that R. peregra and R. ovata are distinct (Glo¨er et al 1987;Ward et al 1997), which is concordant with the 16S data since sequence divergence between these two species is relatively large (8.9%). The tree topologies further show that R. ovata is more closely allied to R. auricularia (bs=76-98%; di=2) than it is to R. peregra.…”
Section: Resultssupporting
confidence: 58%
“…Body growth is indeterminate in Lymnaea although it slows down substantial after about 9-11 months of age in ad libitum fed, captive populations (Janse et al, 1989). In consequence, young sexually mature animals are usually smaller than their more senior conspecifics although body size can differ greatly even within age cohorts (Lam and Calow, 1989a;Lam and Calow, 1989b;Ward et al, 1997) (and own unpublished observations). Although evidence exist that egg-laying slows down and may come to a halt in aged animals (Janse et al, 1989), very few if any studies have systematically investigated male and female copulation incidence across the species' life cycle.…”
Section: Introductionmentioning
confidence: 90%
“…In general, larger animals are older, however, the correlation between size and age is far from perfect. In fact, same-aged snails, including Lymnaea often differ greatly in size and same sized animals might be of different age [present study (Lam and Calow, 1989a;Lam and Calow, 1989b;Ward et al, 1997)]. Thus, size is an unreliable estimate of age and age could be a confounding effect when dealing with size-dependent mating strategies, i.e.…”
Section: Age-versus Size-dependent Matingmentioning
confidence: 99%
See 1 more Smart Citation
“…The snails are commonly considered as variants of the same species because they do not dier in internal anatomy (Hubendick 1951), and because dierences in shell morphology have been found to correspond with enzyme variation only in some, but not in all populations (Lam and Calow 1988;Evans 1989). However, consistent variation between the morphs has been found in shell morphology, population genetic structure, parasite susceptibility (Ward et al 1997), and habitat choice (Wullschleger and Ward 1998). In a laboratory experiment, L. peregra preferred mud over hard substrate, but showed no preference for low or high water level, while L. ovata did not show a preference for a speci®c substrate type, but signi®cantly preferred deeper water (Wullschleger and Ward 1998).…”
Section: Introductionmentioning
confidence: 99%